F(x) = √(5x + 7)
g(x) = √(5x - 7)
(f + g)(x) = f(x) + g(x)
(f + g)(x) = √(5x + 7) + √(5x - 7)
Answer: C)
Answer:
5.4
Step-by-step explanation:
To find the distance between two points,
and
, plug them into the following equation:
![d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\d=\sqrt{(-3-(-8))^2+(-4-(-6))^2}](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28x_2-x_1%29%5E2%2B%28y_2-y_1%29%5E2%7D%5C%5Cd%3D%5Csqrt%7B%28-3-%28-8%29%29%5E2%2B%28-4-%28-6%29%29%5E2%7D)
Two negatives make a positive
![d=\sqrt{(-3+8)^2+(-4+6)^2}\\d=\sqrt{(5)^2+(2)^2}\\d=\sqrt{25+4}\\d=\sqrt{29}\\d=5.4](https://tex.z-dn.net/?f=d%3D%5Csqrt%7B%28-3%2B8%29%5E2%2B%28-4%2B6%29%5E2%7D%5C%5Cd%3D%5Csqrt%7B%285%29%5E2%2B%282%29%5E2%7D%5C%5Cd%3D%5Csqrt%7B25%2B4%7D%5C%5Cd%3D%5Csqrt%7B29%7D%5C%5Cd%3D5.4)
Therefore, the distance between the two points rounded to the nearest tenth is 5.4.
I hope this helps!
Answer:
pls attach the question.....